The effect of capital structure and company size on profit management with profitability as a moderating variable - Kurniawati, Dewi; Munandar, Agus (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Agency problems arise because there is a gap in interests between shareholders or principals as shareholders and agents who are authorized parties or managers to run the company's business. The root of agency problems lies in the division of roles between shareholders, who own capital, and management, who run the company. This research aims to provide empirical evidence regarding the influence of capital structure and company size on earnings management, with profitability as a moderator. The population of this research includes 63 mining sector companies listed on the Indonesia Stock Exchange for the 2018–2021 period. A sample of 17 companies was selected based on the sampling criteria for the intended sampling method. The results of this research indicate that fluctuating capital structures and company size influence revenue management variables. Using the Moderated Regression Analysis (MRA) test shows that profitability can moderate the impact of capital structure on earnings management and can moderate the impact of company size on earnings management. To maintain a good image, management will adopt policies that will affect reporting in the financial statements.